Association between a low baseline level of gene expression of energy metabolism in the blood and the development of clinical remission in response to tofacitinib therapy in patients with rheumatoid arthritis - E. V. Chetina; A. M. Satybaldyev; G. A. Markova; E. Yu. Samarkina; M. V. Cherkasova (Современная ревматология, 2021)
Background. Rheumatoid arthritis (RA) is an autoimmune disease of unknown etiology, characterized by erosive arthritis (synovitis) and systemic inflammation. Janus kinase (JAK) inhibitors (JAKi) are small molecules that block major signal pathways of many cytokines a growth factors, associated with RA. Identification of patients sensitive to JAKi before treatment could significantly improve therapy outcomes. Currently it is not possible to predict JAKi efficacy in every patient, while some patients are non-responsive to the drug, other develop adverse effects. JAKi effect in RA patients has been recently associated with alterations in mitochondrial function and ATP production. Therefore, we hypothesized that baseline metabolic status of RA patients prior to drug administration can predict the therapeutic outcome.Objective: to investigate the predictive value of baseline expression of genes involved in energy generation in the blood of RA patients, for treatment response to JAKi.Patients and methods. We examined peripheral blood of 28 RA patients aged 52.2±15.6 years, average disease duration 3.5 years (range 0.6–19), treated with Tofacitinib (TOFA, 5–10 mg twice a day) during three months and 26 healthy age-matched control subjects. Clinical response was assessed by disease activity score (DAS28-ESR), immunological status by measurements of serum levels of anti-citrullinated protein antibodies (ACPA), rheumatoid factor (RF), and C-reactive protein (CRP). Gene expression was assessed in peripheral blood cells by realtime reverse-transcription polymerase chain reaction (RT-PCR). At baseline all patients had Steinbrocker radiographic stage II–III. Most patients (85.7%) were ACPA and RF positive. Thirteen patients had medium, others – high RA activity.Results and discussion. JAKi treatment significantly decreased the inflammatory disease activity according to DAS28. At the end of the study 17 patients demonstrated moderate disease activity (3.2<DAS28<5.1), 4 patients retained high disease activity while 7, attained remission (DAS28 <2.6). Disease remission, achieved on TOFA treatment, was accompanied by significant decrease in CRP and the number of swollen and tender joints. ESR values were not changed significantly. Gene expression analysis revealed that RA patients, which attained clinical remission after TOFA treatment, demonstrated significantly lower baseline expression of genes associated with glycolysis (pyruvate kinase, PKM2) and oxidative phosphorylation (succinate dehydrogenase, SDHB) compared to other examined RA patients, but higher expression of the abovementioned genes compared to control subjects. Moreover, RA patients who attained clinical remission demonstrated a trend to increase of these gene expressions within follow-up period, while in the rest of patients these gene expression was tending to downregulate.Conclusion. Clinical remission in RA patients treated with JAKi is associated with significantly lower baseline expression of genes associated with energy generation pathways (PKM2 and SDHB) compared to other examined subjects.